Systemic Response of Antioxidants, Heat Shock Proteins, and Inflammatory Biomarkers to Short-Lasting Exercise Training in Healthy Male Subjects. (22nd November 2021) - Dimauro, Ivan; Grazioli, Elisa; Lisi, Veronica; Guidotti, Flavia; Fantini, Cristina; Antinozzi, Cristina; Sgrò, Paolo; Antonioni, Ambra; Di Luigi, Luigi; Capranica, Laura; Caporossi, Daniela
Abstract : Regular physical activity can enhance immune function and effectively prevents the spread of the cytokine response, thus reducing systemic low-grade inflammation and improving various immune markers. Moreover, regular exercise maintains redox homeostasis in skeletal muscle and other tissues, including immune cells, but the interconnection between the anti-inflammatory effects of exercise with the redox status of immune cells is still poorly understood. With the aim to verify the overall beneficial effect of regular training on the immune system, we have examined the acute and short-term effect of a 5-day exercise program on the modulation of protein and lipid oxidation, antioxidants (i.e., superoxide dismutase-1 (SOD1) and superoxide dismutase-2 (SOD2), glutathione peroxide 1 (GPx1), thioredoxin reductase-1 (TrxR1), and catalase (CAT)), and heat shock protein expression (i.e., heat shock protein-70 (HSP70) and heat shock protein-27 (HSP27)), at both mRNA and protein levels, as well as the activation of the nuclear factor kappa light chain enhancer of activated B cells (NF κ B) in peripheral blood mononuclear cells (PBMCs). Moreover, plasmatic markers of oxidative stress, inflammation, and stress response (i.e., protein carbonyl content, interleukin-6 (IL6), interleukin-8 (IL8), interleukin-10 (IL10), interleukin-17E (IL17E), interleukin-17F (IL17F), interleukin-21 (IL21), interleukin-22 (IL22), and interleukin-23 (IL23)) were analyzed in active untrained young adult subjects. Even in the absence of an increased amount of protein or lipid oxidation, we confirmed a PBMC upregulation of SOD1 (1.26 ± 0.07 fold change, p < 0.05 ), HSP70 (1.59 ± 0.28 fold change, p < 0.05 ), and HSP27 gene expression (1.49 ± 0.09 fold change, p < 0.05 ) after 3 hours from the first bout of exercise, followed by an increase in proteins' amount at 24 hours (SOD1, 1.80 ± 0.34 fold change; HSP70, 3.40 ± 0.58 fold change; and HSP27, 1.81 ± 0.20 fold change, p < 0.05 ) and return to basal levels after the 5 days of aerobic training. Indeed, the posttraining basal levels of oxidized molecules in plasma and PBMCs were statistically lower than the pretraining levels (carbonyl content, 0.50 ± 0.05 fold change, p < 0.01 ), paralleled by a lower expression of SOD2, Gpx1, and TrxR1, at mRNA (SOD2, 0.63 ± 0.06 ; GPx1, 0.69 ± 0.07 ; and TrxR1, 0.69 ± 0.12 fold change, p < 0.05 ) and protein (TrxR1, 0.49 ± 0.11 fold change, p < 0.05 ) levels. These results verified the existence of an early phase of redox adaptation to physical exercise already achievable after 5 days of moderate, regular aerobic training. More interestingly, this phenomenon was paralleled by the degree of NF κ B activation in PBMCs and the decrease of plasmatic proinflammatory cytokines IL8, IL21, and IL22 in the posttraining period, suggesting an interconnected, short-term efficacy of aerobic exercise towards systemic oxidative stress and inflammation.